2022
DOI: 10.1007/s10508-021-02209-z
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Health and the Pandemic Crisis: Testing the Role of Psychological Vulnerability/Protective Factors on Sexual Functioning and Sexual Distress During a Critical Life Period in Portugal

Abstract: Recent findings suggest that the current COVID-19 pandemic has a potential negative impact in several areas of life, including sexual health. However, less is known about the psychological dimensions that may work as vulnerability/protective factors for the development of sexual problems in the current pandemic. The current study used a longitudinal design to examine the role played by personality trait factors (neuroticism, extraversion) as well as psychosexual factors (sexual beliefs) in predicting sexual fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 74 publications
0
3
0
Order By: Relevance
“…This study highlighted the fact that psychological traits and beliefs influence people’s response to environmental factors, such as the pandemic. This study may also explain the results of our study—the young age of our study population might have served as a protective factor against sexual dysfunction [ 91 ].…”
Section: Discussionmentioning
confidence: 93%
“…This study highlighted the fact that psychological traits and beliefs influence people’s response to environmental factors, such as the pandemic. This study may also explain the results of our study—the young age of our study population might have served as a protective factor against sexual dysfunction [ 91 ].…”
Section: Discussionmentioning
confidence: 93%
“…For instance, a larger number of participants would enable to evaluate the effect of age, of the type or duration of infertility, and the effect of the protocol (IUI-D versus IVF-D). It is unclear whether COVID-19 pandemic may have impacted results after March 2020 [ 38 ]. However, this is the first study to analyze SD in a population using sperm donation.…”
Section: Discussionmentioning
confidence: 99%
“…Previous findings showed that neuroticism is a higher-order vulnerability factor in the development and maintenance of emotional disorders [30,31] is related to increased risk of development and maintenance of sexual dysfunctions, and is the best predictor of sexual functioning in men [32]. Considered one of the main personality domains [33], neuroticism is associated with emotional instability, worrying tendencies, and increased reactivity to emotionally arousing stimuli [33,34].…”
Section: Neuroticism and Sexual Behaviourmentioning
confidence: 99%